Capacity needs to achieve the UN MDG target 10 in Asia - Ljiljana Rodic-Wiersma; Ram D. Sah (2006)
A preliminary study is conducted in Asia to assess the capacity needs to achieve the UN Millennium Development Goal 7, Target 10 on water supply and sanitation. Needs assessment methodology, compatible with that proposed by the UN Millennium Project, is adopted. Data is gathered by interviewing 66 selected respondents in Bangladesh, China, India and Nepal. In addition, a few projects are analysed for the involvement of professionals. Respondents find that engineers lack managerial skills as well as understanding of social realities. Engineering students are not enough exposed to real-life engineering practice. Curricula and research are insufficiently oriented towards local circumstances and needs. Institutions of higher education lack physical facilities and financial and, consequently, human resources. Analysis of several water supply and sanitation projects reveals that about 20% of professional staff is needed for community mobilisation, in order to ensure the success and sustainability of projects.